Nuevos registros de aves para el Parque Provincial Aconcagua y zonas aledañas, Las Heras, Mendoza, Argentina. Parte II - Ferrer, Diego G.; Bossio, Sergio; Massarelli, Rubén; Traslaviña, Alejandro (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.